The Role of Vitamin E in Peyronie’s Disease - Ricky Suritno (PT Kalbe Farma Tbk., 2018)
Peyronie’s disease (PD) is a disorder of tunica albuginea of corpus cavernosum characterized by the formation of plaque and fibrosis. Oral therapy is a promising non-operative modality. Vitamin E as a well-known antioxidant, is the oldest substance used since 1948 to treat Peyronie’s disease. The mechanism is to inhibit the production of inflammatory reactive oxygen species (ROS). There is still controversy over the effectiveness of vitamin E in Peyronie’s disease management. Penyakit Peyronie merupakan gangguan jaringan ikat tunica albuginea dari corpus cavernosum yang mempunyai karakteristik pembentukan plak dan fibrosis. Terapi oral merupakan modalitas terapi non operatif yang menjanjikan. Vitamin E sebagai antioksidan yang sudah banyak dikenal, merupakan terapi tertua sejak tahun 1948. Mekanismenya adalah untuk menghambat produksi reactive oxygen species (ROS). Sampai saat ini efektivitas vitamin E dalam penanganan penyakit Peyronie masih kontroversial.